Vedolizumab provides clinical benefit over 1 year in patients with active inflammatory bowel disease – a prospective multicenter observational study. Issue 11 (7th October 2016) - Stallmach, A.; Langbein, C.; Atreya, R.; Bruns, T.; Dignass, A.; Ende, K.; Hampe, J.; Hartmann, F.; Neurath, M. F.; Maul, J.; Preiss, J. C.; Schmelz, R.; et al.
Summary: Background: Vedolizumab, a monoclonal antibody targeting the α4β7‐integrin, is effective in inducing and maintaining clinical remission in Crohn's disease and ulcerative colitis according to randomised clinical trials. Aim: To determine the long‐term effectiveness of vedolizumab in a real‐world clinical setting. Methods: This observational registry assessed the clinical outcome in patients treated with vedolizumab for clinically active Crohn's disease ( n = 67) or ulcerative colitis ( n = 60). Primary endpoint was clinical remission (HBI ≤ 4/pMayo ≤ 1) at week 54. Secondary endpoints included clinical response rates (HBI/pMayo score drop ≥3) and steroid‐free clinical remission at weeks 30 and 54. Results: Vedolizumab was stopped in 69/127 (56%) patients after a median time of 18 weeks (range 2–49) predominantly owing to lack or loss of response. Using nonresponder imputation analysis, clinical remission and steroid‐free remission rates were 21% and 15% in Crohn's disease and 25% and 22% in ulcerative colitis, respectively. Lack of clinical remission was associated with prior treatment with anti‐TNF or with steroids for more than 3 months in the last 6 months in ulcerative colitis. At week 14, the absence of remission in Crohn's disease or nonresponse in ulcerative colitis indicated a low likelihood of clinical remission at week 54 [2/31 (7%) in Crohn's disease, 4/41 (10%) in ulcerative colitis]. Accordingly, declining C‐reactive protein in inflammatory bowel disease and/or lower faecal calprotectin in ulcerative colitis at week 14 predicted remission at week 54. Conclusion: Among patients who started vedolizumab for active inflammatory bowel disease, clinical remission rates are 21–25% after 54 weeks.